Combustion synthesis of iron-substituted strontium titanate perovskites - Fumo, Daniel A. (1997)
Perovskites in the system SrO-TiO2-Fe2O3 can be good candidates for electrochemical applications, and the properties of sintered, fully dense bodies depend on the Fe to Ti stoichiometry and the prevailing temperature and oxygen partial pressure. Conductivity studies normally require that the oxides with the desired stoichiometry and structure be synthesized. Solid state synthesis of perovskites requires reasonably high temperatures and full conversion is not guaranteed. Moreover, with this method, it is difficult to obtain a compositionally homogeneous product. The present work discusses a straightforward combustion synthesis technique to prepare submicron iron-substituted Strontium titanate, the Sr(Fe0.5Ti0.5)O-3 perovskite, using the corresponding metal salts-urea mixtures, at low temperature and short reaction times. The effect of the ratio oxidizer/fuel in the redox mixture was investigated, namely to find out how that ratio affected the phase formation and the characteristics, such as morphology and grain size, of the powder produced. Copyright (C) 1997 Elsevier Science Ltd.